Neural basis of intensity-dependent brain activity in response to mechanical stimulation and the level of pain sensitivity - Kawamura, Ryo; Sasaki, Kei; Shimizu, Shunnosuke; Kodama, Naoki (Frontiers in Human Neuroscience, 2026)
IntroductionPain perception greatly varies among individuals and represents a major clinical challenge. Current pain assessment relies on subjective reports; although straightforward, these cannot distinguish the diverse underlying pathophysiological mechanisms of pain. Elucidating brain functional mechanisms using fMRI is crucial for realizing more objective pain assessment. Most studies have focused on thermal stimuli or psychological evaluations, and no studies have focused on differences in sensitivity to mechanical stimulation. Therefore, in this study, we aimed to identify regional differences in brain activation during mechanical stimulation at different intensities using fMRI and to clarify brain activation patterns associated with differences in pain sensitivity between the low- and high-threshold groups.MethodsWe enrolled 52 healthy adults. After measuring mechanical tactile and pain thresholds, fMRI was performed during mechanical stimulation at three intensities (60, 100, and 180 g). Regions of brain activation were identified for each stimulus intensity in all participants and for the high- and low-threshold groups, using the 100-g stimulus as the cutoff value, based on mechanical pain thresholds.ResultsNotable results regarding the change in stimulus intensity are that significant activation was observed in the anterior insular cortex at 60 g; anterior insular cortex, precentral gyrus, and cerebellum at 100 g; and cerebellum, angular gyrus, and thalamus at 180 g of stimulus intensity. Notable results regarding the level of pain sensitivity are that, when classified into the low- (n = 24) and high-threshold (n = 28) groups, activation in the low-threshold group was limited to the somatosensory cortex and its related regions. However, the high-threshold group exhibited activation in the anterior insular cortex, superior parietal lobule, precentral gyrus, and middle frontal gyrus, in addition to the somatosensory cortex.ConclusionThe expansion of brain activation with increasing stimulus intensity suggests the involvement of higher-order central processing, such as attention and response preparation, in noxious stimulus processing. Additionally, differences in pain thresholds may reflect variations in the mode of neural response; the high-threshold group exhibited activation in the frontoparietal network, associated with cognitive control. These findings provide a neurobiological basis for psychological interventions and may serve as a foundation for developing objective biomarkers and advancing personalized pain treatment strategies.